2013
DOI: 10.1371/journal.pone.0081036
|View full text |Cite
|
Sign up to set email alerts
|

Knee Adduction Moment and Medial Contact Force – Facts about Their Correlation during Gait

Abstract: The external knee adduction moment is considered a surrogate measure for the medial tibiofemoral contact force and is commonly used to quantify the load reducing effect of orthopedic interventions. However, only limited and controversial data exist about the correlation between adduction moment and medial force. The objective of this study was to examine whether the adduction moment is indeed a strong predictor for the medial force by determining their correlation during gait. Instrumented knee implants with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
121
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(136 citation statements)
references
References 36 publications
13
121
2
Order By: Relevance
“…We suspect this to be due to an increased lateral evasive movement of the knee during the unilateral STS movement from the low chair height leading to a more medial course of the ground reaction force vector. These findings might be important when executing STS movements with subjects suffering from medial compartment knee osteoarthrosis, as increased knee adduction moments have been associated with increased medial compartment knee joint load [42]. The increasing anterior shear forces observed with decreasing chair height might be explained by a greater contraction of the quadriceps muscle.…”
Section: Effect Of Chair Height On Knee Joint Load During the Unilatementioning
confidence: 87%
“…We suspect this to be due to an increased lateral evasive movement of the knee during the unilateral STS movement from the low chair height leading to a more medial course of the ground reaction force vector. These findings might be important when executing STS movements with subjects suffering from medial compartment knee osteoarthrosis, as increased knee adduction moments have been associated with increased medial compartment knee joint load [42]. The increasing anterior shear forces observed with decreasing chair height might be explained by a greater contraction of the quadriceps muscle.…”
Section: Effect Of Chair Height On Knee Joint Load During the Unilatementioning
confidence: 87%
“…3). However, variability in MTFF across subjects has been shown using instrumented knee implants [39], so it is not surprising to observe such variability in healthy individuals as well.…”
Section: Discussionmentioning
confidence: 99%
“…The KAM has been positively correlated with the shape of MTFF during walking [7, 39], but this is not always the case [3, 4, 37, 40]. Studies based on instrumented tibiofemoral prostheses [41] have shown that decreases in the KAM do not necessarily result in decreases to MTFF [37], and that only small changes occurred in the MTFF for gait patterns designed 1to reduce KAM [42].…”
Section: Introductionmentioning
confidence: 99%
“…The study also identified strategies for proper tuning of this parameter which we used in this study [28]. Although previous investigations have found that the medial-lateral force ratio is correlated with the external knee adduction moment [23,29], it is uncertain as to whether this relationship holds true for all activities and whether it may be influenced by patient characteristics such as knee alignment [30,31]. Specifically, for chair sitting and rising the medial-lateral force ratio of 50%, indicating equal force transfer between the medial and lateral sides of the tibial plateau, was necessary to obtain forces with the computational model.…”
Section: Discussionmentioning
confidence: 99%